Agroforestry Practices and its Relationship to Farmers' Income in Bura'a Mountain Region, Hodaidah Yemen - H. Shoga'a Aldeen, Abdulmoa'amen (2004)
Farmers in Yemen have been practicing traditional agroforestry systems for a long time. These practices provide the main source of income for the local people. The study attempted to examine the agroforestry practices in Bura'a Mountain region of Yemen. The study also examined the relatio~~sh~p between income of farmers and its determinants. The study was conducted through a survey of 130 families in 11 villages at Bura'a Mountain Repon, 118 as agroforestry farmers and 32 as nonagroforestry farmers, by using simple random sampling technique. The primary data were collected from personal interviews with the head of household using a structured questionnaire and some information were collected from published reports available at the FA0 office at Sana'a, General Directorate of Forestry and Desertification Control and Ministry of Agricultural and Irrigation (DGFDC). The study described the agroforestry practices in the area and types of agroforestry systems found are agrisilvicultural, agrosilvopastoral and apiculture. Agrisilvicultural system is common in the highland of Bura'a. The main components of the systems are the perennial crops like coffee and qat with multipurpose trees. The agrosilvopastoral system is found in the plain of Bura'a and the components are the annual crops like sorghum, maze and millet with multipurpose. The apiculture system is also found but not much commonly. About 13.5 percent of the farmers have beehives in the study area. The average income of agroforestry farmers is estimated 345,495 YR (USD 1919.4) per family per year, while the average income of non-agroforestrv farmers is estimatedl62,247 YR (USD 901.4) per family per year. The average income of AF is higher than the average income of NAF farmers. The results of regression analysis indicate that the income of farmers is si@cantly related to the land size holding, number of livestock holding and family size. The results also show that the presence of coffee as a component of the agroforestry system increases farmers' income. Educatwn is also found positively related to the income of the farm household. However, the income is not related to the age of the farmers. The farmers of the study area in need of financial support to increase their production. Some policy recommendations are also highlighted in order to improve agroforestry practices in the region.